A New Approach for Transformer Cooling Systems: Application of Phase Change Materials (PCM) - (:unkn) unknown (POLISH ACAD SCIENCES INST PHYSICS, 2015)
Cooling transformer materials are used for heat storage. In this study, phase change materials (PCM) were investigated in order to use them as alternative materials in cooling systems. PCM materials were tested and the results are presented. A transformer heating model was designed, heating spots were cooled down by application of PCM material to the model transformer. At the end of the study it was observed that heated phase change materials (PCM) kept cool during the same time period, compared to the control experiment.
Keywords: THERMAL-ENERGY STORAGE